2020
DOI: 10.1177/1521025120910714
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Case Study of All-but-Dissertation Students at Risk for Dissertation Noncompletion: A New Model for Supporting Candidates to Doctoral Completion

Abstract: This study identified emergent themes from the interview data of at-risk-for-completion doctoral candidates ( N = 13; 59%), from a diverse demographic, who participated in a successful dissertation completion intervention program. The findings revealed four major themes including extrinsic factors, socioemotional, formal structures of the program, and personal development. The findings highlight the need for conscious processes used by vital leaders to develop program design in four key areas of leadership wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The three components informed and helped foster the development of a friendship that eventually gave rise to compañerismo, which led to the successful navigation of a doctoral program. Research has shown a connection between graduate school's organizational culture and the high propensity for graduate school attrition (Hanson et al., 2020; Lovitts & Nelson, 2000). According to Lovitts (2008), the system of graduate school holds certain norms, values, and beliefs that control the culture of teaching and learning and, at the same time, underscores the relationship between faculty and students.…”
Section: Discussionmentioning
confidence: 99%
“…The three components informed and helped foster the development of a friendship that eventually gave rise to compañerismo, which led to the successful navigation of a doctoral program. Research has shown a connection between graduate school's organizational culture and the high propensity for graduate school attrition (Hanson et al., 2020; Lovitts & Nelson, 2000). According to Lovitts (2008), the system of graduate school holds certain norms, values, and beliefs that control the culture of teaching and learning and, at the same time, underscores the relationship between faculty and students.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of doctoral attrition, however, remains even harder to solve, with scarcer (sometimes, anecdotal) evidence of intervention effectiveness. The attrition interventions that we can find in the literature are often complex, wide-ranging programs like the "Dissertation Completion Grant Program" mentioned by Hanson et al (2020), which had a budget of more than USD6,000 per doctoral student; or the changing of a whole doctoral program to a "collaborative cohort model" to support completion (Colon, 2012); or the whole-program redesign described by McBrayer et al (2018), which expedited time to completion but did not affect overall completion rates.…”
Section: Interventions For Well-being and Dropout In Doctoral Studiesmentioning
confidence: 99%
“…OL Through Flexible Open Systems Souza and Takahashi (2019) explored OL in a higher education setting and agreed that OL "… is a dynamic and multilevel phenomenon… that involves changes in organizations, with social and psychological processes and knowledge flows … Adapting to changes requires flexibility and agility " (p. 397 & 398). Similarly, the Leadership within Open Vital Systems (LOVS) model was developed through qualitative and empirical testing within the context of secondary schools in a northwestern state of the US and in a higher education setting in a private university in the southwestern US (Hanson, 2017;Hanson et al, 2020). The LOVS model works through supporting a common vision of learning including "…healthy social norms to allow flexible structures and the ability for relational learning [necessary for] rapidly changing and complex situations such as within … diverse school populations [and when implementing new technologies]" (pp.…”
Section: Organizational Culture Of Openness and Experimentation (Ex)mentioning
confidence: 99%